2018
DOI: 10.1007/s11999.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Physical Therapy Education Reduces Time to Meet Functional Milestones After Total Joint Arthroplasty

Abstract: Level II, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 26 publications
2
86
0
4
Order By: Relevance
“…Soeters et al 20 implemented preoperative physical therapy education for patients with total joint arthroplasty (hip and knee) that included a one-time, one-on-one educational session with a physical therapist and gave patients access to a microsite providing additional information about postoperative complications, precautions, and mobility. They found that patients reached the criteria for readiness for discharge from physical therapy services in the inpatient setting faster if they had the educational intervention.…”
Section: Preoperative Education ♦◊◊◊mentioning
confidence: 99%
See 1 more Smart Citation
“…Soeters et al 20 implemented preoperative physical therapy education for patients with total joint arthroplasty (hip and knee) that included a one-time, one-on-one educational session with a physical therapist and gave patients access to a microsite providing additional information about postoperative complications, precautions, and mobility. They found that patients reached the criteria for readiness for discharge from physical therapy services in the inpatient setting faster if they had the educational intervention.…”
Section: Preoperative Education ♦◊◊◊mentioning
confidence: 99%
“…The nature of an uncomplicated TKA is not explicit in most studies. Only 1 study implied a definition of uncomplicated by exclusions of patients with “concurrent intervention during surgery that could interfere with outcomes (eg, collateral ligament repair), infection of the affected knee, and any major health complication during the hospital stay (eg, pulmonary embolism, heart attack, problems with scar healing).” 20 …”
Section: Continuous Passive Movement Device (Cpm) Use For Mobilizatiomentioning
confidence: 99%
“…Education must also be provided in all stages of treatment and the repetition of essential items (23). Also, knowledge related to physical therapy was also able to improve patient readiness due to the achievement of physical therapy goals, although this did not affect the length of stay and WOMAC Score (The Western Ontario and McMaster Universities Arthritis Index) (24).…”
Section: Discharge Teachingmentioning
confidence: 99%
“…The perioperative care process around TKA and THA procedures has greatly improved in recent years due to advances in surgical techniques and the introduction of clinical care pathways [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The perioperative care process around TKA and THA procedures has greatly improved in recent years due to advances in surgical techniques and the introduction of clinical care pathways [ 6 , 7 , 8 ]. Clinical care pathways are directed at preparing the patient for discharge as soon as possible after surgery, without compromising outcomes [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%